Bertrand Vs. Cournot: An Evolutionary Approach - Pier Luigi Sacco; Carlo Scarpa (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1992)
In this paper we study an oligopoly game with a differentiated product using a dynamic evolutionary approach. Firms are allowed to choose between quantity setting and price setting behavior. We find that, under both classical interaction structures, namely 'random mating' and 'paying the field'. Quantity setting behavior (i.e., 'Cournot' behavior), is selected as an asymptotically stable state for the dynamics.
Keywords: 330